The Viral of Hadist: Dimensi dan Makna Meme #Hadis Dalam Media Sosial Instagram - Fernando, Henky; Larasati, Yuniar Galuh; Qudsy, Saifuddin Zuhri (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
The dissemination of hadith meme images through the #hadis hashtag on Instagram social media has brought up complex and contextual dimensions and meanings. The studies that have discussed this context have only focused on aspects of communication, so the dimensions and meanings of hadith meme images disseminated on Instagram social media have not been comprehensively explained. This study focuses on the question